Thermoplasmonic Nano–Hybrid Core@Shell Ag@SiO2 Films Engineered via One–Step Flame Spray Pyrolysis - Christos Dimitriou; Yiannis Deligiannakis (Nanomaterials)
Thermoplasmonic heat generation by silver (Ag) nanoparticles can harness visible light to efficiently produce localized heating. Flame spray pyrolysis (FSP) is a powerful one-step synthesis technology for fabricating plasmonic Ag-based nanostructures. In the present study, we employed FSP to engineer core@shell Ag@SiO2 nanoparticles coated with an ultrathin (1–2 nm) silica (SiO2) nanolayer in a single step in tandem with their deposition as films onto solid substrates. Accordingly, we engineered a library of Ag@SiO2 nanofilms with precisely controlled thicknesses in the range of 1–23 μm. A systematic study of the thermoplasmonic heat-generation efficiency (ΔT) of the films under visible-light irradiation (LED, λ = 405 nm) revealed that the films’ compactness and thickness are key parameters governing the heat-generation efficiency and thermal response rate. Moreover, we show that the substrate type can also play a key role; Ag@SiO2 films on glass-fiber filters (PGFFs) enabled faster temperature increase (dT/dt) and a higher maximum temperature gain (ΔTmax) compared with Ag@SiO2 films on glass substrates (PGSs). The photothermal conversion efficiencies were approximately 60%, with the highest efficiency (η = 65%) observed in the thinner impinged film. This study demonstrates that FSP-derived Ag@SiO2 nanofilms provide a versatile and scalable platform for thermoplasmonic heat generation applications with significant industrial potential.